The quality of test on National Examination of Natural science in the level of elementary school - Nurul Hamidah; Edi Istiyono (International Journal of Evaluation and Research in Education (IJERE), 2022)
This research analyzed the quality of National Examination questions on Natural science subjects in elementary schools. The sampling technique used was simple random sampling. Response data were obtained from 250 grade VI elementary school students who responded on the tryout questions. This study was a descriptive study with a quantitative approach to describe the quality of the elementary school science test try-out items. The quality of this question is described quantitatively which includes an index of difficulty level and discriminatory power of questions. The data was collected using a test technique using a test instrument consisting of 30 multiple-choice questions. The analysis was carried out using the BILOG-MG version 4 application to obtain the parameters of distinguishing power and grain difficulty level. Based on the model fit analysis, it was found that the most appropriate model to use for the analysis of the science tryout questions for elementary schools was item response theory (IRT) with the 2PL model. The study concluded that the National Examination questions on science subjects in elementary schools had met the criteria for the level of difficulty and distinguishing power so that they could be said to be in a good category.